Humanities Analysis in the Context of Sustainable Development; Gender, Justice, and Economic Empowerment - Alpa Ahmadi; Antika Salman Paris; Nattapat Tanwattana; Nini Arianti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Gender issues and economic justice increasingly occupy a central position in the discourse of sustainable development. The gender gap that still exists in various sectors, especially in access to education, employment, and asset ownership, shows the need for a more comprehensive strategy in realizing social justice. This article discusses how humanities perspectives, especially gender studies, moral philosophy, and sociology, can provide a deeper understanding of the power relations between men and women in an economic context. Through a literature review, this article highlights the importance of women's economic empowerment as a strategic step in achieving the Sustainable Development Goals (SDGs), especially on goal 5 (gender equality) and goal 8 (decent work and economic growth). The results of the study show that economic empowerment not only increases women's independence, but also creates a multiplier effect on family and community welfare. However, challenges in the form of patriarchal culture, structural discrimination, and limited access to technology are still obstacles. Therefore, an inclusive, participatory, and local wisdom-based gender-based approach is needed so that the transformation towards socio-economic justice can be achieved in a sustainable manner.